Pancasila Ideology in Political Education Programs - Syintia Nurain Hudjolly; Ratna Sari Dewi (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Pancasila is the source of everything related to the nation and state which reflects the soul of the nation (Volkgeist). In the life of the Indonesian people, in realizing the spirit of the nation, a political party was formed which is an important element as a supporter of the success of a democratic country. Therefore the Gelora Party as a political party needs to build and have good political will in the form of unity, attitude to defend and love the Indonesian people. Political education is the foundation for political parties which need to comply with the Pancasila Ideology. The condition of Indonesian society where some of them do not fully understand Pancasila Ideology needs to be guided, one of which is through political parties. The implementation of political party members in practicing political education needs to be maximized. So that the obstacles that occur in political education programs can be overcome. This research is based on the Theory of Policy Implementation and Theory of Constraints, with a type of qualitative research, as well as descriptive research methods. In this study, researchers looked for studies that were relevant to the research being conducted, reviewing existing research. Public apathy towards politics is one of the inhibiting factors, besides that the Indonesian Gelora Party is a new party which is constrained by human resources. The efforts made by the Regional Leadership Council of the Indonesian Wave People Party in Tangerang Regency in carrying out political education have been quite good through joint discussion forums to social media. The obstacle or obstacle faced by the Regional Leadership Council of the Indonesian Wave People Party in Tangerang Regency is having to compete with long-established political parties.